Histone Deacetylase Inhibitor I3 Induces the Differentiation of Acute Myeloid Leukemia Cells with t (8; 21) or MLL Gene Translocation and Leukemic Stem-Like Cells. (28th August 2022) - Zhao, Mengjie; Duan, Yu; Wang, Jiangyun; Liu, Yong; Zhao, Yao; Wang, Haihua; Zhang, Lei; Chen, Zhe-Sheng; Hu, Zhenbo; Wei, Liuya
Abstract : Acute myeloid leukemia (AML) is a heterogeneous disorder characterized by the clonal expansion and differentiation arrest of leukemic cells in peripheral blood and bone marrow. Though the treatment using cytarabine-based protocol for AML patients with t (8; 21) translocation has improved the 5-year overall survival rate, drug resistance continues to be the principal limiting factor for the cure of the disease. In addition, very few AML patients with mixed lineage leukemia gene rearrangements (MLLr) have a desirable outcome. This study evaluated the cell differentiation effect of a potent HDAC (histone deacetylase) inhibitor, I3, and its possible mechanism on the AML cells with t (8; 21) translocation or MLLr and leukemic stem-like cells (Kasumi-1, KG-1, MOLM-13, and THP-1). I3 exhibited efficient anti-proliferative activity on these cells via promoting cell differentiation, accompanied by the cell cycle exit at G 0/ G 1. Importantly, I3 showed the properties of HDAC inhibition, as assessed by the acetylation of histones H 3 and H 4, which resulted in blocking the activation of the VEGF (vascular endothelial growth factor)-MAPK (mitogen-activated protein kinase) signaling pathway in the Kasumi-1 cell line. These data demonstrate that I3 could be a potent chromatin-remodeling agent to surmount the differentiation block in AML patients, including those with t (8; 21) translocation or MLLr, and could be a potent and selective agent for AML treatment.